Incidence, Pattern and Mortality of Traumatic Abdominal Injury, a Three‐Year Study at the Largest Trauma Center in Southern Iran: A Cross‐Sectional Study - Mahnaz Yadollahi; Hosein Fazeli; Mehdi Ghasemian; Mohammad Reza Yousefi; Mehrdad Karajizadeh; Hanie Farajpour (Health Science Reports, 2025)
ABSTRACT Background and Aims Trauma remains a significant contributor to global mortality rates, with abdominal trauma being a prevalent diagnosis among traumatic patients and often leading to substantial mortality rates. The objective of this study was to investigate the nature of abdominal trauma, ascertain associated injury characteristics, and identify independent factors associated with mortality in patients referred to a level‐one trauma center located in the southern region of Iran. Methods This cross‐sectional study was conducted at the largest trauma center in the southern region of Iran from June 2018 to June 2021. The study included all adult patients diagnosed with abdominal trauma based on the criteria outlined in the Abbreviated Injury Scale guidelines. Data were collected on patient characteristics, injury anatomy, injury mechanism, duration of hospitalization, blood pressure levels, injury severity, and outcomes. Results The study analyzed 844 cases among 4755 individuals admitted to the emergency department (17.75% prevalence) with an 18.40% mortality rate. Liver injuries were associated with increased mortality, while spleen injuries, although common, were not. Most patients were male, with an average age of 36. The most common causes were road traffic accidents and falls, with blunt trauma being predominant. Variables with observed association with mortality included age (p value < 0.001, OR = 1.057), GCS = 3–8 (p value < 0.001, OR = 10.780), retroperitoneal hemorrhage (p value < 0.001, OR = 3.052), higher ISS (p value < 0.001, OR = 1.039), and length of hospital stay (p value = 0.002, OR = 0.974). Conclusion This study highlights the significant burden of abdominal trauma on mortality rates in traumatic patients. Understanding the nature and predictors of abdominal trauma can help improve outcomes and guide future interventions in trauma care.